2014
DOI: 10.1073/pnas.1417549111
|View full text |Cite
|
Sign up to set email alerts
|

Loss of p53 induces cell proliferation via Ras-independent activation of the Raf/Mek/Erk signaling pathway

Abstract: The Ras family of small GTPases constitutes a central node in the transmission of mitogenic stimuli to the cell cycle machinery. The ultimate receptor of these mitogenic signals is the retinoblastoma (Rb) family of pocket proteins, whose inactivation is a required step to license cell proliferation. However, little is known regarding the molecular events that connect Ras signaling with the cell cycle. Here, we provide genetic evidence to illustrate that the p53/ p21 Cdk-interacting protein 1 (Cip1)/Rb axis is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(78 citation statements)
references
References 35 publications
4
74
0
Order By: Relevance
“…Loss of p53 was recently found to induce cell proliferation via Ras-independent activation of the Raf/Mek/Erk signaling pathway (70). In line with these findings, overexpression of p53 is known to inhibit cell proliferation (71,72).…”
Section: Discussionmentioning
confidence: 73%
“…Loss of p53 was recently found to induce cell proliferation via Ras-independent activation of the Raf/Mek/Erk signaling pathway (70). In line with these findings, overexpression of p53 is known to inhibit cell proliferation (71,72).…”
Section: Discussionmentioning
confidence: 73%
“…This screen unambiguously identified the Trp53/Cdkn1a (p53/p21Cip1) tumor suppressor axis as an essential mediator of Ras mitogenic signaling. 7 Indeed, efficient knockdown of either p53 or p21Cip1 expression fully restored the proliferative properties of Rasless cells (Fig. 1B).…”
mentioning
confidence: 82%
“…Further studies revealed that loss of Ras proteins caused widespread transcriptional activation of p53 through a mechanism involving acetylation of 2 specific residues in its DNA binding domain. 7 Surprisingly, phosphorylation and/or protein stabilization of p53 was not required. These genetic studies place the p53/p21 axis at the center of the mitogenic pathway that connects Ras signaling with the cell cycle (Fig.…”
mentioning
confidence: 99%
“…We have recently shown that absence of the p53/ p21Cip1/Rb axis indeed causes such a Ras-independent Raf/Mek/ Erk activation and allows proliferation of Rasless MEFs [ 9 ]. No rescue in the absence of p53, p21Cip1, or Rb was observed in Rafl ess, Mekless, or Erkless cells, indicating that, in contrast to Ras proteins, the Raf, Mek, or Erk kinases were absolutely essential for cell proliferation.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, addition of a membrane-attachment domain to the Raf kinases was suffi cient to bypass the requirement for Ras proteins, thus suggesting that the major function of Ras proteins in mitogenic signaling is to recruit Raf kinases to the membrane, where activation of their kinase activity must occur independently of Ras [ 8 ]. Likewise, genetic elimination of the three Raf isoforms (A-Raf, B-Raf, c-Raf), both Mek (Mek1 and 2) or both Erk isoforms (Erk1 and 2) caused a cell cycle arrest phenotype indistinguishable from that of Rasless cells [ 9 ]. Taken together, these observations indicate that activation of the Raf/Mek/Erk pathway by Ras proteins is both necessary and suffi cient to sustain cell proliferation.…”
Section: Introductionmentioning
confidence: 99%